Flushing Time of Shatt Al-Arab River, South of Iraq - Abdullah, S.S.; Lafta, A.A.; Al-Taei, S.A.; Al-Kaabi, A.H. (Mesopotamian Journal of Marine Sciences, 2022)
Flushing time for tidal rivers and estuaries is of great benefits for those involved in taking appropriate decisions in water resources management. Shatt Al-Arab River is the main and only source of fresh water to Basra City, South of Iraq. Unfortunately, this river is facing an environmental deterioration as a result of presence of many pollution sources. The calculated flushing time of the river helps to estimate the expected time needed to renew the river water. Fresh water fraction method was used to calculate flushing time. The results showed that three factors are responsible for affecting the value of flushing time. These factors are upstream coming flow discharge, phenomenon of tide and lastly the location distance from the estuary. The results also showed that the flushing time of the northern part of the river from Maqal port until the confluence with Karun River are much more than that of southern part. Results also showed that the flushing time for the whole parts of the river was 2.4 months.